Preemption and Rent Equalization in the Adoption of New Technology - Fudenberg, Drew; Tirole, Jean (Review of Economic Studies, 1985)
We study the adoption of a new technology to illustrate the effects of preemption in games of timing. We show that the threat of preemption equalizes rents in a duopoly, but that this result does not extend to the general oligopoly game. If the gain to preemption is sufficiently small, then the optimal symmetric outcome, which involves “late” adoption, is an equilibrium. This contrasts with Reinganum's result that in precommitment equilibria there must be “diffusion”. We develop a new and richer formalism for modeling games of timing, which permits a continuous-time representation of the limit of discrete-time mixed-strategy equilibria.